THE P5 AND PPRA MODEL IN INCLUSIVE SCHOOLS - Siti Fatimah; Muhamad Chamdani (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract This study aims to determine the P5 and PPRA models (Projek Penguatan Profil Pelajar Pancasila and Profil Pelajar Rahmatan Lil ‘Alamin) as a Project of Strengthening Pancasila Student Profiles and Student Profile of Rahmatan Lil' Alamin in Inclusive Schools and their supporting and inhibiting factors. The subjects in this study were inclusive elementary schools in Kebumen, namely SD Negeri 2 Pejagoan and MI Maarif Sidomulyo. This study used a qualitative approach with a type of phenomenology. Data collection was through observation, interviews, and documentation. Analysis techniques used were the Miles and Huberman model, namely condensation, display, and conclusion/verification data. The results of the analysis indicated that the P5 and PPRA model in inclusive schools had been outlined in the annual program and school semester program, which were then developed in the flow of learning objectives and teaching modules, making them flexible according to the characteristics of students with special needs. The existence of good partnerships between schools, families, and the community was the dominant factor supporting P5 and PPRA, and the lack of learning facilities and media was an inhibiting factor in strengthening P5 and PPRA.